Comparison of efficacy of various drugs used for medical expulsive therapy for distal ureter stones: A systematic review and network meta‐analysis. Issue 9 (20th April 2021) - Sharma, Gopal; Kaundal, Pawan; Pareek, Tarun; Tyagi, Shantanu; Sharma, Aditya P.; Devana, Sudheer K.; Singh, Shrawan K.
Abstract: Objectives: Medical expulsive therapy has been found to be effective for distal ureteric stones; however, which drug is most efficacious in terms of stone expulsion rate (SER) and stone expulsion time (SET) is not known. With this review we aimed to compare the efficacy of various drug treatments for distal ureter stones used as medical expulsive therapy in terms of SER and SET. Methods: Systematic literature search was conducted to include all the randomised study comparing various drug interventions for lower ureter stones. Standard preferred reporting items for systematic review and meta‐analysis for network meta‐analysis (PRISMA‐NMA) were pursued. Results: In this review, 50 randomised studies with 12, 382 patients were included. For stone expulsion rate (SER), compared with placebo all the treatment groups were more effective except nifedipine and sildenafil. According to the SUCRA values obtained, naftopidil plus steroid was the highest rank and nifedipine lowest. For stone expulsion time (SET), compared with placebo only tadalafil plus silodosin, nifedipine plus steroid, alfuzosin, silodosin, tadalafil and tamsulosin were more effective. SUCRA values were highest for tadalafil plus silodosin and least for naftopidil plus steroid. From subgroup analysis with individual drugs for SER, SUCRA values were highest for naftopidil followed by silodosin and SET was highest for silodosin and least for naftopidil. Conclusion: For lower ureter stone, tadalafil plus silodosin is the best combination and silodosin best individual drug considering the SET and SER. Nifedipine as monotherapy is no more effective than control group.